Pengukuran User Experience Pada Aplikasi Simulasi Kebakaran Keselamatan Dan Kesehatan Kerja Berbasis Augmented Reality - Bisma Khairunnas; Riwinoto Riwinoto (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2022)
Occupational safety and health is very important to learn, one of which is fire disaster management. But to do learning in fire management, it takes time and adequate space. Fire simulation application is an application that utilizes augmented reality technology to facilitate users in learning and understanding how to deal with fire disasters if they occur indoors. However, to make fire simulation applications attractive and make users feel satisfied, user experience measurements must be made to determine the level of user satisfaction. To get user experience measurements, research was conducted using the Quality in use Integrated Measurement (QUIM) method where this method determines quality requirements such as identifying, analyzing, and validating processes and quality metrics in augmented reality-based fire simulation applications. QUIM which has 10 consolidated model factors for its assessment, namely efficiency, effectiveness, satisfaction, productivity, learnability, safety, trustfulness, accessibility, universality, and usefulness. data collection by means of users will test the application first. After that, a questionnaire will be given, this is done in a closed manner where users can only answer "yes" and "no". Based on the analysis and data that has been processed in this study, after obtaining the data, it will be processed by producing a value for each factor and the average of the whole is 70.86% which has a "good" category. In the productivity factor by producing a value of 86.66% in the "very good" category and the lowest value in the effectiveness factor with a value of 60% in the "sufficient" category.